Transformation of the Legislative System in Indonesia Based on the Principles of Good Legislation - Martitah, Martitah; Hidayat, Arif; Anitasari, Rahayu Fery; Rahman, Malik Akbar Mulki; Aini, Triska Rahmatul (Universitas Negeri Semarang, 2023)
The Constitutional Court’s decision (Number 91/PUU-XVIII/2020) on the Formal Examination of Law Number 11 of 2020, addressing Job Creation and the subsequent enactment of Law Number 13 of 2022, has catalyzed a profound transformation in Indonesia’s legal system. This legal evolution, explored in the context of the Transformation of the Legislative System in Indonesia Based on the Principles of Good Legislation, delves into the political dynamics of legislation leading to numerous Constitutional Court litigations. The quality of law formation is scrutinized in light of the principles of good legislation, emphasizing transparency, participation, effectiveness, and efficiency. The study assesses how the Indonesian parliament executes its legislative function and underscores the imperative for reformulating planning, institutions, and capacity. The article advocates for an expedited authorization of Information and Communication Technology (ICT) as a crucial step toward digitizing legislation in the pursuit of a thoroughly transformed and principled legislative system.